Examining the Level of Sports Science Faculty Students' Knowledge of Computer Game Dependency - Tutar, Ömer Faruk; Kırtepe, Abdurrahman; Nacar, Eyyup (My University, 2020)
The aim of our study was to examine the computer game dependence levels of the students ofFaculty of Sports Sciences in terms of some variables. The research group of our study consists of 453randomly selected undergraduate students at Firat University, Faculty of Sports Sciences in 2018. A personalinformation form (department, class, age, gender, computer game playing status, time of game playing) a 20-question computer games dependence scale based on adapting Young's(1998) dependency scale intocomputer games were applied to determine the demographic information of the subjects involved in thestudy. Frequency of variables(f) and percentage(%) distributions were calculated and duplex varianceanalysis(ANOVA) was used in multiple group variables and t-test was used for the significance of thedifference between the two independent groups. Tukey test was used to determine which groups it wasamong in the analysis which significant differences were detected. The error level in the study was taken asp<0,05. According to the study's findings, undergraduate students in the faculty of sports sciences at FiratUniversity; Depending on the department, class and age variables in which studied, it was determined thatthere was no statistically significant difference in the computer game dependency levels of the undergraduatestudents. There was a significant difference between levels of game dependency based on gender, computergame play status and daily playing time variables. According to the study findings, computer game addictionscores of undergraduate students in the faculty of sports sciences at Firat University averaged 42.90 andcomputer gaming addiction levels above average. Games contribute to people's mental development andcause various harms in uncontrolled use. It is thought that the monitoring and control of family members isimportant in our young people's playing these games.
Keywords: Spor Bilimleri